2018
DOI: 10.1088/1674-1056/27/11/110501
|View full text |Cite
|
Sign up to set email alerts
|

Bursting oscillations as well as the bifurcation mechanism in a non-smooth chaotic geomagnetic field model

Abstract: Based on the chaotic geomagnetic field model, a non-smooth factor is introduced to explore complex dynamical behaviors of a system with multiple time scales. By regarding the whole excitation term as a parameter, bifurcation sets are derived, which divide the generalized parameter space into several regions corresponding to different kinds of dynamic behaviors. Due to the existence of non-smooth factors, different types of bifurcations are presented in spiking states, such as grazing-sliding bifurcation and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Then, Qu et al [22] further investigated a more complex double excitation non-smooth Filippov system and discovered the multi-sliding bifurcation oscillation phenomenon. And Zhang et al [23] found that introducing a non-smooth factor into the chaotic geomagnetic field model can lead to the phenomenon of grazingsliding bifurcation and cross-sliding bifurcation. In addition, Leutcho et al [24,25] studied chaotic hyperjerk circuits and revealed the phenomenon of mixed-mode bursting oscillations and various coexisting Feigenbaum remerging trees.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Qu et al [22] further investigated a more complex double excitation non-smooth Filippov system and discovered the multi-sliding bifurcation oscillation phenomenon. And Zhang et al [23] found that introducing a non-smooth factor into the chaotic geomagnetic field model can lead to the phenomenon of grazingsliding bifurcation and cross-sliding bifurcation. In addition, Leutcho et al [24,25] studied chaotic hyperjerk circuits and revealed the phenomenon of mixed-mode bursting oscillations and various coexisting Feigenbaum remerging trees.…”
Section: Introductionmentioning
confidence: 99%
“…e introduction of the slow-fast dynamics analysis method [19] well explained the bifurcation connection between the spiking state and the quiescent state, so as the mechanism of bursting oscillation. Based on this method, various bursting oscillation modes [20][21][22][23][24][25][26][27][28][29][30][31][32][33] are obtained, such as fold/fold bursting and fold/ Hopf bursting. In nonlinear dynamical system, two time scales can lead to complex dynamical behavior of the system, so it is widely concerned by academic circles domestically and overseas.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [53] presented an algorithm for computing 2D stable and unstable manifolds of hyperbolic fixed points of nonlinear maps, and its performance was demonstrated by hyperchaotic 3D HĂ©non map and Lorenz system. Zhang et al [54] and Han et al [55] discussed the dynamical behaviors of bursting oscillations. Zhang et al [56] studied the existence and stability of the Hopf bifurcation of a modified Pan-like chaotic system.…”
Section: Introductionmentioning
confidence: 99%